Nunnery scene: a pragmatic analysis of hamlet-ophelia encounter - Qaisar Khan,; Faraz Ali Bughio, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
In the recent past, the emergence of Pragmatics has added to the value of contextual intentions of speakers in a conversation. It has led to various research studies analysing utterances from a linguistic point of view exploring the words and sentences that constitute them. This research study aims to pragmatically analyse the dialogic patterns in a Shakespearian masterpiece, Hamlet. For the purpose of the study, the Nunnery Scene (Act III, Scene I) has been selected for pragmatic analysis with particular reference to context, cooperative principle, conversational maxims of Grice and implicature in qualitative paradigm. The findings reveal that these concepts are significant to the proper understanding and appreciation of the conversation.